La estimulación acuática y su incidencia en el desarrollo psicomotriz en los niños de seis a doce meses de edad en la Academia Fisiokids de la ciudad de Guayaquil - Manzo Fuentes, Karla Andrea (2020)
Aquatic stimulation is an important technique for children six to twelve months old in their sensorimotor part, muscle tone, coordination, balance, posture, safety;; even though there are numerous investigations into the subject. In Ecuador there are several swimming schools where aquatic stimulation classes are improperly provided to children, these schools have teachers with swimming degrees but lack of certifications in Aquatic Stimulation. The goal of this research is to analyze the influence of aquatic stimulation on the psychomotor development of children aged six to twelve months…..